The Interplay Between Time Management, Motivation and Academic Performance Among University Students - Makiah, Makiah; Nusron, Anis (Faculty of Economics and Business, Universitas Klabat, 2025)
This study examines the relationship between time management and motivation on academic performance among university students. The objective of the research is to explore how these factors influence academic outcomes and to address inconsistencies in prior findings. A quantitative methodology was employed, targeting the entire student population of a private university in East Java, Indonesia. Data were collected through a structured questionnaire distributed via Google Forms, ensuring convenience and accessibility. Pearson Correlation analysis was used to assess the relationships between the variables. The results revealed that time management was not significantly associated with academic performance, while motivation demonstrated a significant positive correlation with academic outcomes. These findings underscore the importance of fostering motivation and cultivating positive attitudes to enhance academic success. The study highlights practical implications for educators and policymakers in designing interventions that target motivational factors to improve student performance in higher education settings.